A novel gallium oxide nanoparticles-based sensor for the simultaneous electrochemical detection of Pb2+, Cd2+ and Hg2+ ions in real water samples - Gehad Abd El-Fatah; Hend S. Magar; Rabeay Y. A. Hassan; Rehab Mahmoud; Ahmed A. Farghali; Mohamed E. M. Hassouna (Scientific Reports, 2022)
Abstract Differential pulse voltammetry (DPV) using gallium oxide nanoparticles/carbon paste electrode (Ga2O3/CPE) was utilized for the simultaneous detection of Pb2+, Cd2+ and Hg2+ ions. Ga2O3NPs were chemically synthesized and fully characterized by Fourier-transform infrared (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Through the assay optimization, electrochemical screening of different nanomaterials was carried out using the cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) in order to determine the best electrode modifier that will be implemented for the present assay. Consequently, various parameters such as electrode matrix composition, electrolyte, deposition potential, and deposition time were optimized and discussed. Accordingly, the newly developed sensing platform showed a wide dynamic linear range of 0.3–80 µM with detection limits (LODs) of 84, 88 and 130 nM for Pb2+, Cd2+ and Hg2+ ions, respectively. While the corresponding limit of quantification (LOQ) values were 280, 320 and 450 nM. Sensors selectivity was investigated towards different non-targeting metal ions, whereas no obvious cross-reactivity was obtained. Eventually, applications on real samples were performed, while excellent recoveries for the multiple metal ions were successfully achieved.